Modeling and analysis of performance and emissions of marine lean-burn natural gas engine propulsion in waves. (1st December 2020) - Tavakoli, Sadi; Saettone, Simone; Steen, Sverre; Andersen, Poul; Schramm, Jesper; Pedersen, Eilif
Abstract: In many vessels, the prime mover is a diesel engine, while the researchers recommended using natural gas as an attractive option to comply with the latest emission legislations. This study aims to analyze the dynamic response of a spark-ignition engine fueled by natural gas. Due to the complexity of power system operation in transient conditions, ship propulsion modeling is performed to assess the environmental impact of dynamic load. A co-simulation modeling in MATLAB- SIMULINK platform was developed to couple the medium-speed, four-stroke, turbocharged, spark-ignition engine to a propeller immersed in seawater. The engine's essential elements were implemented, and the validity of the modeling was evaluated using the manufacturer's data in both steady-state and transient conditions. The main goal was to determine the importance of the transient loads on the engine response, particularly during harsh weather conditions. Hence, simulations of various wave conditions with multiple wave amplitude, wave direction, and wavelength were conducted. Compared with the steady-state, the transient condition resulted in a deterioration of the combustion efficiency. Furthermore, the amount of unburned fuel, NOX compounds, and brake specific fuel consumption have increased. Highlights: A co-simulation model is performed to simulate a lean-burn natural gas engine connected to a propeller. The model is validated using the available results of the operating engine. This model enables detailed insight into the response of the engine in dynamic loads. The model predicts emission formation in rapid transient conditions.